Chad : Staff Report for the 2003 Article IV Consultation; and Ex Post Assessment of Performance Under ESAF/PRGF Programs. (IMF Staff Country Reports; Country Report ;, 2004)
Chad has succeeded in recent years in broadly maintaining macroeconomic stability and a high growth rate of economic activity. There has been a significant effort to formulate the detailed modalities for the use of oil revenues so as to ensure that oil revenues are used transparently and efficiently in the fight against poverty. It is essential to maintain an appropriate fiscal expenditure policy. Executive Directors urge the government to sustainably improve public expenditure management. Improving non-oil fiscal revenue performance is essential for eventually attaining fiscal sustainability.